2014
DOI: 10.1016/j.neurobiolaging.2014.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Choriocapillaris breakdown precedes retinal degeneration in age-related macular degeneration

Abstract: This work presents a combined light and electron microscopical approach to investigate the initial breakdown of the retinal pigment epithelium (RPE) and choriocapillaris (CC) in age-related macular degeneration (AMD). Perimacular sections of 12 dry and wet AMD eyes (82 ± 15 years) and 7 age-matched controls (75 ± 10 years) without retinal pathology were investigated. Disease progression was classified into 5 stages of retinal degeneration to investigate the concurrent CC breakdown. Special emphasis was laid on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
205
2
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(217 citation statements)
references
References 35 publications
6
205
2
4
Order By: Relevance
“…Another study by Moult et al [48] found focal regions of CC flow alteration underlying nascent GA and drusen-associated GA as well as a diffuse CC flow impairment throughout the imaged field. These preliminary results underscore the theory that CC breakdown precedes RPE and photoreceptor degeneration [7]. CC flow impairment at the margin of GA may also be a potential predictor of GA growth with regards to both growth direction and growth rate [49].…”
Section: Octa In Dry Amdsupporting
confidence: 61%
See 2 more Smart Citations
“…Another study by Moult et al [48] found focal regions of CC flow alteration underlying nascent GA and drusen-associated GA as well as a diffuse CC flow impairment throughout the imaged field. These preliminary results underscore the theory that CC breakdown precedes RPE and photoreceptor degeneration [7]. CC flow impairment at the margin of GA may also be a potential predictor of GA growth with regards to both growth direction and growth rate [49].…”
Section: Octa In Dry Amdsupporting
confidence: 61%
“…The production of trophic factors, including vascular endothelial growth factor (VEGF) by the RPE, ensures CC survival, while CC atrophy results in tissue hypoxia accelerating RPE and photoreceptor dysfunction [5]. A recent histopathologic study by Biesemeier et al [7] suggests that changes in CC precede the degeneration of the RPE in AMD. Whether alterations in the CC are in fact the primary event in nonexudative AMD or secondary to molecular changes in the RPE is still a matter of debate.…”
Section: Octa In Dry Amdmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23] In contrast, AMD as a multifactorial disease showed inconsistent histopathologic results as there may be transition zones from intact to absent CC as well as CC breakdown preceding outer retinal degeneration. 9,24,25 In this context, hypofluorescence in areas of RPE atrophy during late phases of indocyanine green angiography (ICGA), used to visualize choroidal vasculature, 26,27 was found to be more common in STGD1 compared to AMD. 28 The introduction of optical coherence tomography angiography (OCT-A) allows for noninvasive in vivo visualization of blood flow with three-dimensional resolution.…”
mentioning
confidence: 99%
“…[1][2][3][4] The early and intermediate stages of the disease are characterized by the accumulation of drusen and a slow loss of the choriocapillaris. [5][6][7] Initially, both stages are associated with minimal impairment of visual acuity. 3,8,9 However, in advanced AMD, loss of vision can be caused by either exudative neovascular (''wet'') AMD or geographic atrophy (GA).…”
mentioning
confidence: 99%